Dietary Intake of Parkinson's Disease Patients - Baert, Florence; Matthys, Christophe; Mellaerts, Randy; Lemaître, Dirk; Vlaemynck, Geertrui; Foulon, Veerle (Frontiers in Nutrition, 2020)
Background & Aims: Dietary management, as an adjuvant therapy in Parkinson’s disease (PD), provides clear benefits to patients. However, baseline information about the usual dietary intake of Parkinson’s patients is lacking. Methods: We conducted an observational cross-sectional study, investigating the dietary intake in Belgian PD patients, as well as their medication use and knowledge of possible food-drug interactions. A dietary record of two non-consecutive days, allowing the calculation of usual intake, was used. Medication use and knowledge of food-drug interactions were investigated using a self-administered questionnaire. Results: The nutrient (both macro and micro) intake in this study was similar to the dietary pattern of the general Belgian population. However, results showed that the PD population had a high dietary fiber intake of 26.2±7.7g/day, which is in line with the recommended intake. The majority of the PD patients had an inadequate intake of vitamin D and iron (respectively 55.9% and 76.5% of all participants). When looking into the knowledge about food-drug interactions, the majority of the PD patients claimed to be aware of the food-drug interaction between dietary proteins and levodopa. However, only 18.2% of the patients took all doses of levodopa out of meals. Conclusion: Our results show that monitoring of dietary intake in PD patients is of importance to detect possible micronutrient insufficiencies. Patients should receive professional guidance in optimizing their diet to accommodate for different complaints inherent to PD, including constipation. Furthermore, the knowledge of patients regarding the importance of correct medication intake should be improved.